2017
DOI: 10.1186/s13098-017-0257-6
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to explore the perception and behavior of patients towards diabetes management with physical disability

Abstract: BackgroundThis study aimed to determine self-monitoring practices, awareness to dietary modifications and barriers to medication adherence among physically disabled type 2 diabetes mellitus patients.MethodsInterview sessions were conducted at diabetes clinic—Penang general hospital. The invited participants represented three major ethnic groups of Malaysia (Malay, Chinese and Indians). An open-ended approach was used to elicit answers from participants. Interview questions were related to participant’s percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Because it was not feasible to perform a community-based face-to-face survey during this period, we conducted a telephone-based qualitative interview study in young adults with T1DM. Similar qualitative interview studies have been used in the past to assess the experiences, perceptions, behaviors and psychosocial aspects of people living with diabetes mellitus [ [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. Although telephone-based qualitative interview has generally been considered inferior to in-person interviews [ 22 ], using telephone for qualitative interviews carries with it the logistic and practical advantages of improved access to geographically dispersed interviewees, reduced costs and increased interviewer safety [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because it was not feasible to perform a community-based face-to-face survey during this period, we conducted a telephone-based qualitative interview study in young adults with T1DM. Similar qualitative interview studies have been used in the past to assess the experiences, perceptions, behaviors and psychosocial aspects of people living with diabetes mellitus [ [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. Although telephone-based qualitative interview has generally been considered inferior to in-person interviews [ 22 ], using telephone for qualitative interviews carries with it the logistic and practical advantages of improved access to geographically dispersed interviewees, reduced costs and increased interviewer safety [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Glycemic control is one of the ultimate tools to evaluate the patient’s disease progression and treatment success [ 3 , 6 ] however, clinical literature showed that not only treatment but patient’s perception and self-care behavior are also strong mediating factors for glycemic control among T2DM patients [ 3 , 6 , 8 , 11 ]. Several studies have shown positive effect of self-care management to glycemic index [ 4 , 7 , 9 11 ], also diabetic-related knowledge is considered as an important factor for development/improvement in self-care behavior and practices [ 12 ]. Similarly, chronic or long term complications reduce the well-being of patient with adverse changes on self-care behavior thus resulted with poor HRQOL and decrease health status/state [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-care is the one of the important factor for achieving optimal glycemic levels among patients with IDDM [ 2 , 3 ]. Diabetes patients are responsible for their daily care, such as self-monitoring blood glucose (SMBG), diet management, and insulin dose adjustments [ 5 , 6 ]. Diabetes affects the daily life functioning therefore, lowering the health status and QOL among patients [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment success or failure also based on patient's satisfaction to different aspects of disease domains [ 1 , 6 ]. Diabetes is often examined in terms of compliance and metabolic outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation